Hubungan Karakteristik Kontainer dengan Keberadaan Jentik Nyamuk Aedes aegypti di Wilayah Kerja Puskesmas Poasia Kota Kendari - La Ode Alifariki; Mubarak Mubarak (Halu Oleo University, 2017)
ABSTRACT Date of DHF patients in the working area of Poasia Health Center of Kendari City shows that in 2015 31 people, where in January 6 patients, February 10 patients, while in 2016 as many as 48 patients ie January 1 patients and February 2 patients. In the year 2017 ie in January there were no patients and in February as many as 7 patients and there is 1 patient died. From these data it can be concluded that almost every month in every year occur DHF incidence, because DHF is a contagious disease and endemic disease that quickly lead to death if not handled appropriately. This study aims to determine the relationship of kontainer characteristics with the presence of larvae Aedes aegypti mosquitoes in the working area of Poasia public health center of kendari city. The type of this research is observational research with cross sectional study approach.The population in this study is all the houses in the working area of Poasia Health Center of Kendari City. samples of 85 samples. the statistical test used is chi square and phi test. The results showed that there was a correlation of kontainer material (X2hit) = 4,504 and φ = 0,258), kontainer location (X2hit) = 4,032 and φ = 0,242), kontainer color (X2hit) = 4,210 and φ = 0,246), condition of kontainer cover (X2hit ) = 5,171 and φ = 0,279) with presence of Aedes aegypti mosquito larvae. The public is expected to raise awareness in considering the condition of kontainers such as the color of bright kontainers, the kontainers must always be closed, the kontainer is not made of soil and glass and improve the behavior of Mosquito Nest Eradication.Keywords: Aedes aegypti mosquito larvae, kontainer characteristicsABSTRACT Date of DHF patients in the working area of Poasia Health Center of Kendari City shows that in 2015 31 people, where in January 6 patients, February 10 patients, while in 2016 as many as 48 patients ie January 1 patients and February 2 patients. In the year 2017 ie in January there were no patients and in February as many as 7 patients and there is 1 patient died. From these data it can be concluded that almost every month in every year occur DHF incidence, because DHF is a contagious disease and endemic disease that quickly lead to death if not handled appropriately. This study aims to determine the relationship of kontainer characteristics with the presence of larvae Aedes aegypti mosquitoes in the working area of Poasia public health center of kendari city. The type of this research is observational research with cross sectional study approach.The population in this study is all the houses in the working area of Poasia Health Center of Kendari City. samples of 85 samples. the statistical test used is chi square and phi test. The results showed that there was a correlation of kontainer material (X2hit) = 4,504 and φ = 0,258), kontainer location (X2hit) = 4,032 and φ = 0,242), kontainer color (X2hit) = 4,210 and φ = 0,246), condition of kontainer cover (X2hit ) = 5,171 and φ = 0,279) with presence of Aedes aegypti mosquito larvae. The public is expected to raise awareness in considering the condition of kontainers such as the color of bright kontainers, the kontainers must always be closed, the kontainer is not made of soil and glass and improve the behavior of Mosquito Nest Eradication.Keywords: Aedes aegypti mosquito larvae, kontainer characteristics